"Is it us or is it me?": Family experiences of connectedness following a reflecting team intervention. (8th November 2020) - Browne, Dillon T.; Norona, Jerika; Busch, Amy; Armstrong, Keith; Crouch, Sarah; Ernst, Teo; Darrow, Sabrina; Smith, Jackson A.; Ihle, Eva C.
Abstract: The present study examined family‐wide versus individual perceptions of, and changes in, family connectedness in response to a one‐time reflecting team (RT) intervention. Seventy‐six families ( N  = 208 individuals), recruited during family therapy, completed family connectedness measures before and after the RT intervention. A subset of adults ( n  = 26) completed 1‐week follow‐up measures. Three‐level (family, individual, time) multilevel models were used to partition sources of variance in connectedness while permitting different fixed and random effects for adults and minors. Results indicate that family connectedness is a characteristic of whole‐families (34% of the variance), individuals (43%), and change over time (23%), including measurement error. Additionally, participants reported higher family connectedness after the RT. This study demonstrates the importance of considering family connectedness as a multilevel relationship construct that potentially changes in response to RT.